Challenges to the Leadership Position of the European Union in World Trade - Moraliyska, Monika (Research Papers, 2022)
The aim of the article is to determine whether the EU is a world trading power and what the challenges are for maintaining its position in the future. The applied methodology includes: statistical data analysis, descriptive analysis, comparative analysis, SWOT analysis, induction and deduction. The result shows that the EU is a strong trading power globally and that it uses that both for economic benefits and to influence its trading partners in are as >such as as social rights and sustainable development. It depends on the EU’s cooperation with key partners, as well as on linking trade policy to the new challenges.